Qualidade de Vida no Trabalho (QVT): as percepções dos servidores de uma Companhia de Águas e Esgotos em uma unidade no interior de Rondônia - Ribeiro, Sabrina Neres (2024)
The aim of this study was to analyze the perceptions of the employees of a water and sewage company in a city in the interior of the state of Rondônia on aspects related to quality of life at work (QWL). The structure of this work was organized based on the presentation of two articles. The first was developed with the aim of carrying out a systematic review of the literature on QWL, which included scientific articles published between January 2014 and April 2023 available in the Scopus and Web of Science databases. The results indicated fluctuations in the number of publications over the years, with a peak in 2018, a greater focus on health professionals and an expansion into the hospitality sector. It was found that among the articles there was collaboration between authors from different countries, a predominance of theoretical-empirical, cross-sectional and quantitative studies, with emphasis on the use of the Structural Equation Modeling (SEM) technique in data analysis. The second article sought to analyze the perceptions of the employees of the Companhia de Águas e Esgotos on aspects related to QWL. Fourteen career civil servants took part in this study. They answered a sociodemographic and work-related form, and 12 of them answered an interview about QWL in their work environment. The data was analyzed using content analysis. The results showed that the respondents' perceptions of what they understood by QWL differed from those of the QWL actually provided by the Water and Sewage Company. In the company's work environment, the categories Socio-professional Work Relationships and Work-Social Life Link were those with the highest number of positive aspects in the respondents' assessment, unlike others such as Recognition and Personal Growth, Work Organization and Working Conditions, in which many challenging aspects to QWL were identified, and it should be noted that the latter was pointed out as one of the main desirable elements for achieving quality of life in the workplace. All the results of this study have helped to show that QWL continues to be a current and constantly evolving discussion in the academic world and have made it possible to reflect on the work context of the employees of the Water and Sewage Company, by identifying critical areas and suggesting strategies for promoting QWL in the company.